Brief Reports - Alectinib Dose Escalation Reinduces Central Nervous System Responses in Patients with Anaplastic Lymphoma Kinase–Positive Non–Small Cell Lung Cancer Relapsing on Standard Dose Alectinib. Issue 2 (February 2016) - Gainor, Justin F.; Chi, Andrew S.; Logan, Jennifer; Hu, Ranliang; Oh, Kevin S.; Brastianos, Priscilla K.; Shih, Helen A.; Shaw, Alice T.
Abstract : ABSTRACT: : The central nervous system (CNS) is an important and increasingly recognized site of treatment failure in anaplastic lymphoma kinase (ALK)‐positive, non–small cell lung cancer (NSCLC) patients receiving ALK inhibitors. In this report, we describe two ALK‐positive patients who experienced initial improvements in CNS metastases on standard dose alectinib (600 mg twice daily), but who subsequently experienced recurrences with symptomatic leptomeningeal metastases. Both patients were dose‐escalated to alectinib 900 mg twice daily, resulting in repeat clinical and radiographic responses. Our results suggest that dose intensification of alectinib may be necessary to overcome incomplete ALK inhibition in the CNS and prolong the durability of responses in patients with CNS metastases, particularly those with leptomeningeal carcinomatosis.